(untitled) (Bangladesh Journal of Educational Research, 2026)
This study was conducted to explore the consistencies between learning outcomes and the contents of climate change issues in the Bangladesh and Global Studies (BGS) curriculum and textbooks at the lower secondary level. BGS textbooks for grades six, seven, and eight were selected to conduct this study. The researchers primarily focused on the climate change issue as a current social need of the learners. A qualitative methodology was employed to gain a comprehensive understanding, and data were collected by analysing related documents and conducting interviews with BGS secondary school teachers and curriculum experts. The researchers used a semi-structured interview schedule to record data from the respondents. The collected data was analysed thematically. A significant finding of this study identified that the textbook contents on climate change issues are consistent to a considerable extent with the learning outcomes of the lower secondary level curriculum. Besides that, the study also found that more pictures and content on specific topics will be more conducive to the learners. Based on the findings, the researchers have suggested some recommendations.